Omega-3 Fatty Acids and Vitamin D Decrease Plasma T-Tau, GFAP, and UCH-L1 in Experimental Traumatic Brain Injury - Scrimgeour, Angus G.; Condlin, Michelle L.; Loban, Andrei; DeMar, James C. (Frontiers in Nutrition, 2021)
Traumatic brain injury (TBI) results in neuronal, axonal and glial damage. Interventions targeting neuroinflammation to enhance recovery from TBI are needed. Exercise is known to improve cognitive function in TBI patients. Omega-3 fatty acids and vitamin D reportedly reduce inflammation, and in combination, might improve TBI outcomes. This study examined how an anti-inflammatory diet affected plasma TBI biomarkers, voluntary exercise and behaviors following exposure to mild TBI (mTBI). Adult, male rats were individually housed in cages fitted with running wheels and daily running distance was recorded throughout the study. A modified weight drop method induced mTBI, and during 30 days post-injury, rats were fed diets supplemented with omega-3 fatty acids and vitamin D3 (AIDM diet), or non-supplemented AIN-76A diets (CON diet). Behavioral tests were periodically conducted to assess functional deficits. Plasma levels of Total tau (T-tau), glial fibrillary acidic protein (GFAP), ubiquitin c-terminal hydrolase L1 (UCH-L1) and neurofilament light chain (NF-L) were measured at 48h, 14d and 30d post-injury. Fatty acid composition of food, plasma and brain tissues was determined. In rats exposed to mTBI, NF-L levels were significantly elevated at 48h post-injury (P<0.005), and decreased to levels seen in uninjured rats by 14d post-injury. T-tau, GFAP and UCH-L1 plasma levels did not change at 48h or 14d post-injury. However, at 30d post-injury, T-tau, GFAP and UCH-L1 all significantly increased in rats exposed to mTBI and fed CON diets (P<0.005), but not in rats fed AIDM diets. Behavioral tests conducted post-injury showed that exercise counteracted cognitive deficits associated with mTBI. The AIDM diets significantly increased docosahexaenoic acid levels in plasma and brain tissue (P<0.05), and in serum levels of vitamin D (P<0.05). The temporal response of the four injury biomarkers examined is consistent with studies by others demonstrating acute and chronic neural tissue damage following exposure to TBI. The anti-inflammatory diet significantly altered the temporal profiles of plasma T-tau, GFAP and UCH-L1 following mTBI. Voluntary exercise protected against mTBI-induced cognitive deficits, but had no impact on plasma levels of neurotrauma biomarkers. Thus the prophylactic effect of exercise, when combined with an anti-inflammatory diet, may facilitate recovery in patients with mTBI.